2021
DOI: 10.1007/s40617-021-00578-4
|View full text |Cite
|
Sign up to set email alerts
|

Racial Prejudice and Police Stops: A Systematic Review of the Empirical Literature

Abstract: A police stop must be based on founded suspicion, an officer's ability to correctly discriminate suspicious behavior. However, police stops can be influenced by negative attitudes towards Black individuals. We conducted a systematic review of empirical articles published from 2014 until 2019 that investigated the relationship between racial prejudice and police stops on PsycInfo, using keywords such as "race", "ethnic", "police stop", "traffic stop", and "stop and frisk". Results included 16 studies conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Research on racial profiling in traffic stops has consistently shown that the driver's race and ethnicity influences police decision-making (e.g. Barnum and Perfetti, 2010;Carroll and Gonzalez, 2014;Carvalho et al, 2022;Vito et al, 2017;Zhang and Zhang, 2021). A longstanding problem with this research, however, is the limited information about the effects of legal and other extra-legal factors on traffic stop outcomes (Batton and Kadleck, 2004;Engel et al, 2002).…”
Section: Research On Racial Profiling and Traffic Stopsmentioning
confidence: 94%
“…Research on racial profiling in traffic stops has consistently shown that the driver's race and ethnicity influences police decision-making (e.g. Barnum and Perfetti, 2010;Carroll and Gonzalez, 2014;Carvalho et al, 2022;Vito et al, 2017;Zhang and Zhang, 2021). A longstanding problem with this research, however, is the limited information about the effects of legal and other extra-legal factors on traffic stop outcomes (Batton and Kadleck, 2004;Engel et al, 2002).…”
Section: Research On Racial Profiling and Traffic Stopsmentioning
confidence: 94%
“…The occupational culture and practices of police departments can influence the execution and consequences of stop-and-search operations. Officer discretion, training guidelines, supervisory methods and performance indicators might influence the incidence, targeting and behaviour during these encounters [16].…”
Section: Factors Beyond Police Responsibilitymentioning
confidence: 99%
“…Minority men often experience stigmatization that is unique in their demographic background, and they may consequently consider the experience not only as an experience of racial stigmatization but also gender stigmatization. For example, a Black man may construe his experience of police brutality (Carvalho et. al., 2021) not only as racial discrimination but also as gender discrimination ("I wouldn't have experienced this if I were a woman").…”
Section: Additive Multiplicative and Projective Approachesmentioning
confidence: 99%